Comparing the application of Health Information Technology in primary care in Denmark and Andalucía, Spain - Protti, Denis; Johansen, Ib; Perez-Torres, Francisco (International journal of medical informatics (Shannon, Ireland), 2009)
It is generally acknowledged that Denmark is one, if not the, leading country in terms of the use of information technology by its primary care physicians. Other countries, notably excluding the United States and Canada, are also advanced in terms of electronic medical records in general practitioner offices and clinics. This paper compares the status of primary care physician office computing in Andalucía to that of Denmark by contrasting the functionality of electronic medical records (EMRs) and the ability to electronically communicate clinical information in both jurisdictions. A novel scoring system has been developed based on data gathered from databases held by the respective jurisdictional programs, and interviews with individuals involved in the deployment of the systems. The scoring methodology was applied for the first time in a comparison of the degree of automation in primary care physician offices in Denmark and the province of Alberta in Canada. It was also used to compare Denmark and New Zealand. This paper is the third offering of this method of scoring the adoption of electronic medical records in primary care office settings which hopefully may be applicable to other health jurisdictions at national, state, or provincial levels. Although similar in many respects, there are significant differences between these two relatively autonomous health systems which have led to the rates of uptake of physician office computing. Particularly notable is the reality that the Danish primary care physicians have individual “Electronic Medical Records” while in Andalucía, the primary care physicians share a common record which when secondary care is fully implemented will indeed be an “Electronic Health Record”. It is clear that the diffusion of technology, within the primary care physician sector of the health care market, is subject to historical, financial, legal, cultural, and social factors. This tale of two places illustrates the issues, and different ways that they have been addressed.